Potential health risk assessment for fluoride and nitrate contamination in hard rock aquifers of Shanmuganadhi River basin, South India. Issue 1 (17th February 2019) - Karunanidhi, D.; Aravinthasamy, P.; Subramani, T.; Wu, Jianhua; Srinivasamoorthy, K.
Abstract: A detailed investigation was carried out in Shanmuganadhi basin, South India, to delineate the fluoride and nitrate concentrations in groundwater and their impacts on human health. Sixty-one groundwater samples were collected and examined for several parameters such as pH, EC, TDS, Ca 2+, Mg 2+, Cl −, HCO3 −, Na +, K +, SO4 2−, NO3 −, PO4 3− and F − . The results of the study indicate that 23% and 49% of the groundwater samples exceed the permissible limits of fluoride and nitrate for consumption, respectively. Therefore, consumption of F − - and NO3 − -rich groundwater could cause health hazards. To evaluate the health risk, total hazard index (THI) and hazard quotient (HQ) were computed based on the United States Environmental Protection Agency (USEPA) guidelines. The results of the assessment indicate that the total non-carcinogenic risks for children and adults (men) range from 0.02 to 7.66 and from 0.1 to 5.67, respectively. Furthermore, 80% and 69% of the samples surpass the recommended limit of the THI (HQ > 1) for children and men, respectively. It suggests that children are more vulnerable than adults (men) for health risk in Shanmuganadhi basin.